Digital Competence and Technology Adaptation as Determinants of Work Innovation of MSMEs Actors in Regional Arts and Culture Performances (PSBD) in Asahan Regency In 2025 - Julianda, Nirda; Afandi, Adi Mas; Matondang, Ramadan; Tarigan, Hikmat Syahputra (The Es Economics and Entrepreneurship, 2025)
This study aims to analyze the influence of digital competence and QRIS payment technology adaptation on the work innovation of MSMEs at the Regional Arts and Culture Center (PSBD) of Asahan Regency. The research approach used was quantitative with a survey method of 40 MSMEs participating in the 2025 Asahan PSBD activities. Data were analyzed using multiple linear regression to determine the influence of digital competence (X₁) and QRIS technology adaptation (X₂) on work innovation (Y). The results of the study indicate that the digital competence of MSME HR has a positive and significant effect on work innovation with a significance value of 0.032, while QRIS adaptation also has a significant effect with a significance value of 0.021. The simultaneous test (F) shows that both variables together have a significant effect on work innovation with a calculated F value of 12.832 (p < 0.05). The coefficient of determination (R²) of 0.531 indicates that 53.1% of the variation in work innovation is influenced by digital competence and QRIS adaptation. These findings underscore the importance of strengthening the human resource capacity of MSMEs through digital literacy and readiness to adopt technology to encourage sustainable work innovation. Generation Z has high digital literacy and is quickly mastering digital platforms. They excel at content creation, business social media use, and digital analytics.